Virtual reality and augmented reality in plastic surgery: A review - Kim, Y.; Kim, H.; Kim, Y.O. (Korean Society of Plastic and Reconstructive Surgeons, 2017)
Recently, virtual reality (VR) and augmented reality (AR) have received increasing attention, with the development of VR/AR devices such as head-mounted displays, haptic devices, and AR glasses. Medicine is considered to be one of the most effective applications of VR/AR. In this article, we describe a systematic literature review conducted to investigate the state-of the- art VR/AR technology relevant to plastic surgery. The 35 studies that were ultimately selected were categorized into 3 representative topics: VR/AR-based preoperative planning, navigation, and training. In addition, future trends of VR/AR technology associated with plastic surgery and related fields are discussed. ？ 2017 The Korean Society of Plastic and Reconstructive Surgeons.
Keywords: human; plastic surgery; simulation; systematic review; virtual reality